LITHIUM ISOTOPIC SIGNATURES OF PERIDOTITE XENOLITHS AND ISOTOPIC FRACTIONATION AT HIGH TEMPERATURE BETWEEN OLIVINE AND PYROXENES - Seitz H.M.; Brey G.P.; Lahaye Y.; Durali S.; Weyer S. (My University, 2004)
We determined the Li isotopic composition of coexisting olivine, clinopyroxene, and orthopyroxene from spinel- and garnet-bearing peridotite xenoliths from San Carlos (Arizona), Vitim (Siberia), Dreiser Weiher (Eifel, Germany), and Kapfenstein (Austria). These samples represent the upper mantle that experienced varying degrees of partial melting followed by different metamorphic and metasomatic histories. Ultrasonic cleaning of handpicked mineral separates with Milli-Q water (18 MΩ cm) removed significant amounts (10–30%) of the lithium from unwashed separates and resulted in systematically heavier lithium isotopic compositions in the washed minerals. δ7Li values for washed minerals range from +1.4‰ to +4.5‰ in olivines, from −1.0‰ to +3.9‰ in orthopyroxenes, and from −2.4‰ to +3.0‰ in clinopyroxenes, δ7Li=[(7Li/6Li)sample/(7Li/6Li)L-SVEC standard−1]×1000. Olivines in mildly depleted lherzolites (Eifel, Vitim, San Carlos) are isotopically the heaviest (δ7Li +3.4–+4.5‰). A metasomatised, amphibole-bearing lherzolite from the Eifel gave the lightest value (+1.4‰). Olivines have similar δ7Li values to that of MORB, while the pyroxenes are isotopically lighter. In all but one sample, the δ7Li changes systematically between the minerals; olivine has the heaviest δ7Li value followed by orthopyroxene, and clinopyroxene has the lightest values. The degree of intramineral fractionation (Δδ7Li=[δ7Liol−(δ7cpx)]) correlates negatively with equilibration temperature. Δδ7Li is about 3.5 for low-temperature (∼950 °C) xenoliths and 1.5 for high-temperature (~1150 °C) xenoliths. We therefore suggest Li isotope fractionation may occur at high, magmatic temperatures.